ANALISIS KINERJA PEGAWAI DAN SISTEM KOMPENSASI DI ERA DIGITAL PADA KANTOR KEMENTERIAN AGAMA KABUPATEN NIAS - Tasya Sawitri Telaumbanua; Palindungan Lahagu; Eliagus Telaumbanua; Meiman Hidayat Waruwu (Jurnal Publikasi Manajemen Informatika, 2026)
This study aims to analyze employee performance and the effectiveness of the compensation system in the digital era at the Ministry of Religious Affairs Office, Nias Regency. The increasingly rapid digital transformation demands that government officials adapt to information technology to improve efficiency, transparency, and the quality of public services. However, this change also presents challenges in terms of human resource readiness, limited digital competency, and the effectiveness of the implemented compensation system. This study used a qualitative descriptive method with data collection techniques through interviews, observation, and documentation. The results show that the level of employee readiness for digitalization varies, influenced by factors such as competence, motivation, and organizational support. Employee performance is determined by work quality, quantity, timeliness, effectiveness, and independence, all of which are strongly influenced by the work environment and leadership. Meanwhile, the existing compensation system is not yet fully effective in increasing employee motivation and loyalty, due to challenges related to fairness and suitability to the needs of the digital era. This research is expected to provide strategic input for relevant agencies to improve employee performance and refine compensation systems amidst the demands of digitalization.